Japonia i Kanada – od konkurencji do przyjaźni? - Nowak, Katarzyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
This piece characterizes the relationship between Japan and Canada. It contains the parts dedicated to the history, culture, economy and politics. It describes the cooperation of these countries in international organizations e.g. APEC or G7. The author basing on the theory of the international relations, especially neo-liberalism, tries to forecast the nature of the future relations of Japan and Canada
Keywords: Japan; Canada; International Relations; politics; economics; bilateralism; Asia-Pacific; neoliberalism; analysis